(3SeW GdfLhe GdYhGdi aj CfHGA GdChGFd GdJhGdis - (3YHO Gdedc Hf MSjf Hf YHO Gdedc GdYUGei Gdecj GdTGaYj,J (B1111 (3g` s ((3YHO GdYRjR Hf YHO Gddg YeQ Hf YHO GdYRjR Hf Shjde s)
(3ChdgG (B:s
(3hjNai Gfg cGf dHfi YHO efGa ai bQjT eMd ef GdYOO hGdTQa ajg CMO ef HWhf bQjT s
(3BNQgG (B:s
(3afeJ HGHgi efXQ hCRgi fXGe hdeG cGf jhe GdNGeS ef Pi GdMLI GdMQGe gPG BNQ eG hLOfGg ecJhHkG ai GdfSN s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdCejQ YHO Gddg Hf YHO GdQMef Bd SYhO GdNGUI HGdQjGV s
Keywords: (3GdJGQjNs